Fecal Carriage and Epidemiology of Extended-Spectrum Beta-Lactamase/Carbapenemases Producing Enterobacterales Isolates in Bulgarian Hospitals - Rumyana Markovska; Petya Stankova; Temenuga Stoeva; Dobrinka Ivanova; Daniela Pencheva; Radka Kaneva; Lyudmila Boyanova (MDPI AG, 2021)
The gastrointestinal tract is an important reservoir of extended spectrum beta-lactamase (ESBL)/carbapenemase-producing Enterobacterales isolates. This study included patients from two Bulgarian hospitals. Overall, 98 ESBL producers (including 68 Escherichia coli and 20 Klebsiella pneumoniae isolates) were detected among 99 hospitalized patients, 212 patients at admission, and 92 hospital staff in 42.4%, 24.5%, and 4%, respectively. We observed blaCTX-M-15 in 47% of isolates, blaCTX-M-3 in 39% and blaCTX-M-14 in 11%. Three blaCTX-M-15 positive isolates were also blaKPC-2 positive. High transferability was detected for blaCTX-M-3 carrying plasmids (55%) with L/M and I1 replicon plasmids, followed by CTX-M-14 (36.4%) and CTX-M-15 (27.9%) with IncF plasmids. BlaKPC-2 was carried by FIIAs plasmids. Epidemiology typing revealed 8 K. pneumoniae ST types-ST15(8/20), ST17(4/20), ST37(2/20) and 9 E. coli ST types-ST131 (30.9%, 21/68), ST38 (8/68), ST95(7/68) and ST316(7/68). All ST131 isolates but one was from the highly virulent epidemic clone O25bST131. This is the first report in Bulgaria about ESBL/carbapenemase faecal carriage. We observed high ESBL/carbapenemases prevalence. A predominant number of isolates were members of highly epidemic and virulent PanEuropean clones ST15 K. pneumoniae and O25bST131 E. coli. High antibiotics usage during the COVID pandemic will worsen the situation. Routine screenings and strict infection control measures should be widely implemented.